Hubungan Pengetahuan, Dampak dan Persepsi Terhadap Minat Merdeka Belajar Kampus Merdeka - Martanty Aditya; Fibe Yulinda Cesa; Godeliva Adriani Hendra (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2023)
This study aims to determine the dependencies between several aspects, including knowledge, impact, and perceptions of Pharmacy students on interest in the MBKM program. The research method used an observational design on all Ma Chung University Malang Pharmacy students. The research instrument was a questionnaire from the survey. spadadikti.id page. The data obtained was then analyzed using the chi-square test. The results showed the existence (p-value <0.05) in several significant aspects, including general knowledge, general impact, length of study, improvement of soft skills, fulfillment of post-campus needs, increased competence, document readiness, and readiness of MBKM. This research result showed that the higher of knowledge level, the higher the interest in MBKM. Regarding perception, the higher the good, the higher the perception of the impact of MBKM. This study also showed no significant dependency on readiness; generally, they are ready to join the MBKM program. However, there is a considerable dependency related to the willingness of the Pharmacy Study Program in terms of documents; respondents with high interest will know more about the existence of MBKM documents. The role of the Study Program is needed in terms of socialization and document readiness for Pharmacy students. It is expected to increase student interest so that they are more optimal in participating in MBKM.